GC–MS profiling of Bacillus spp. metabolites with an in vitro biological activity assessment and computational analysis of their impact on epithelial glioblastoma cancer genes - Naveed, Muhammad; Ishfaq, Huda; Rehman, Shafique Ur; Javed, Aneela; Waseem, Muhammad; Makhdoom, Syeda Izma; Aziz, Tariq; Alharbi, Metab; Alshammari, Abdulrahman; Alasmari, Abdullah F. (Frontiers in Chemistry, 2023)
Bacterial metabolites are very essential to human beings and have been used successfully for the treatment of numerous diseases. In the current study, the 16S rRNA method and streaking were used to isolate and molecularly identify the bacterial strain. The aim of current study is to characterize the potential bioactive volatile bacterial metabolites extracted by nonpolar and polar solvents. The GCMS analysis identified twenty-nine compounds with varying retention times and peak areas, including the main compounds found in Bacillus spp. which are 2-Propanone, 4,4-Ethylenedioxy-1-pentylamine, 1,2-Benzenedicarboxylic acid, 1,1-Butoxy-1-isobutoxy-butane, and 3,3-Ethoxycarbonyl-5 hydroxytetrahydropyran-2-one. According to the literature, these molecules have numerous biological and pharmacological applications. Different concentrations were used to analyze and treat the biological activity of the metabolites produced from Bacillus species. Bacterial metabolites inhibit anti-diabetic activity (84.66%), anti-inflammatory activity (99%), antioxidant activity (99.8%), and anti-hemolytic activity (90%). These metabolites were also tested for bioactivity using the disc diffusion method and demonstrated a significant inhibitory effect against the tested strains. Additionally, the in-silico screening of the discovered bacterial compounds on the epithelial glioblastoma cancer gene revealed that 1, 2-Benzenedicarboxylic acid had anticancer activity and had advantageous drug-designing properties. The potential of Bacillus spp. as a drug research target for bioactive metabolites was discussed in this study. The findings suggest that bacterial metabolites are a significant source of strains with a variety of beneficial traits that may be useful in the production of biological antibacterial agents.